Therapeutic potential of 4-hexylresorcinol in reducing sarcopenia in diabetic masseter muscle - Dhouha Gaida; Young-Wook Park; Yei-Jin Kang; Seong-Gon Kim (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background This study aimed to evaluate the effects of 4-hexylresorcinol (4HR), a synthetic compound with antioxidant and stress-modulating properties, on diabetic sarcopenia in the masseter muscle. Methods A controlled, parallel-arm study was conducted using 38 Sprague–Dawley rats divided into diabetic and non-diabetic groups. Diabetes was induced with streptozotocin (STZ), and the groups were further subdivided to receive weekly subcutaneous injections of either 4HR or saline. Muscle volume was assessed using micro-computed tomography (μCT), and glycogen storage and protein expression were analyzed using periodic acid-Schiff (PAS) staining and immunohistochemistry. Results μCT analysis revealed that diabetic rats exhibited significantly reduced masseter muscle volume compared to non-diabetic rats. However, 4HR treatment partially mitigated muscle volume loss in diabetic animals. Histological analysis showed higher PAS staining intensity in the diabetic group treated with 4HR compared to the untreated diabetic group, suggesting improved glycogen storage. Immunohistochemistry demonstrated that 4HR treatment significantly increased Glut4 and phosphorylated AMPKα (p-AMPKα) expression in diabetic muscle, indicating enhanced glucose uptake and metabolic activity. Conclusions 4HR effectively alleviates diabetes-induced sarcopenia by preserving muscle volume, enhancing glycogen storage, and upregulating Glut4 and p-AMPKα expression. These findings suggest that 4HR holds potential as a therapeutic agent for combating muscle wasting in diabetes.